Childhood and anarchist culture in Rosario de Santa Fe, 1890–1930 (Estudios Sociales, 2024)
In Argentina, historians have made important contributions to our understanding of the relationship between childhood and leftist politics. Despite this, our conception of ‘anarchist childhoods’ – and of what could be called the ‘anarchist life cycle’ – remains relatively limited. Therefore, this article examines the interactions between children and adults in the Argentine anarchist movement and delves into the ways in which anarchists understood childhood. The analysis focuses on the city of Rosario de Santa Fe, drawing on the contemporary press, and archival material produced by the local authorities and activists of the late-nineteenth and early-twentieth centuries. The central contribution of this work is its definition of anarchist pedagogy and parenting as forms of ‘prefigurative politics’: encapsulating the ideals of the movement, they became means of constructing, in the present, the future anarchist society.
Keywords: Childhood; anarchism; education; play; prefiguration